Pengaruh Kemudahan, Fitur Layanan dan Promosi Penjualan Terhadap Keputusan Penggunaan Dompet Digital ShopeePay pada Aplikasi Shopee di Kabupaten Kebumen - Pratiwi, Riska; Fitra, Joko (LP3M Universitas Putra Bangsa, 2023)
This study aims to determine the effect of ease, service features, and sales promotions on the decision to use the ShopeePay digital wallet in Kebumen Regency. This study uses a purposive sampling technique, by taking a sample of 100 respondents to ShopeePay digital wallet users who have made transactions. This study uses data analysis techniques using descriptive and statistical analysis techniques including validity testing, reliability testing, classical assumption testing, hypothesis testing, coefficient of determination, and multiple linear analysis using the SPSS 24 for Windows program. The results showed that ease, service features, and sales promotions partially had a positive effect on the decision to use the ShopeePay digital wallet. The results of the study show that the variables of ease, service features, and sales promotions simultaneously have a positive effect on the decision to use the ShopeePay digital wallet. The R² value of the equation is 0.525 meaning that the variable of the decision to use (dependent) which is explained by the variable ease, service features, and sales promotion (independent) in this study was 52,5%, while 47,5% was influenced by other variables not explained by this study.